The Influence of School Principal Leadership and Work Environment on Teacher Work Motivation in Elementary School - Solekha, Siti; Sumarno; Rasiman (Belajea: Jurnal Pendidikan Islam, 2024)
This study investigates the impact of school principal leadership and work environment on elementary school teachers’ work motivation in Sarwas 3, Pemalang District. Using a correlational quantitative approach with 130 teacher respondents, data were analyzed via linear regression. Results show that principal leadership significantly influences teacher motivation, contributing 61.2%, while work environment contributes 30.7%. Together, they explain 62.5% of the variance in motivation. Key factors include interpersonal leadership and managerial support. The findings highlight the crucial role of effective leadership and supportive work environments in enhancing teacher motivation and performance. Recommendations focus on improving leadership skills and fostering a culture of recognition to sustain teacher motivation.